2021
DOI: 10.3390/cancers13194960
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine and Cholesterol Plasma Levels and Clinical Outcomes of Patients with Metastatic Castration-Resistant Prostate Cancer Treated with Taxanes

Abstract: Altered metabolism is a hallmark of cancer. Malignant cells metabolise glutamine to fulfil their metabolic needs. In prostate cancer, androgen receptor signalling promotes glutamine metabolism, which is also involved in cholesterol homeostasis. We aimed to determine whether the plasma glutamine levels correlate with the blood lipid profile, clinical characteristics and outcomes in patients with metastatic castration resistance prostate cancer (mCRPC) undergoing taxanes. We retrospectively assessed the glutamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…32 On the other hand, lipid metabolism played an important role in the LVSI of type 2 EC, mainly consisting of nonendometrioid adenocarcinoma. Many studies have shown that cholesterol is closely related to the metastasis of hormone-dependent tumors, such as prostate cancer, 33 breast cancer, 34 and EC. 35 In addition, Kho et al performed a bidirectional, two-sample Mendelian randomization analysis to investigate the relationship between levels of three blood lipids and EC risk in a large population.…”
Section: Discussionmentioning
confidence: 99%
“…32 On the other hand, lipid metabolism played an important role in the LVSI of type 2 EC, mainly consisting of nonendometrioid adenocarcinoma. Many studies have shown that cholesterol is closely related to the metastasis of hormone-dependent tumors, such as prostate cancer, 33 breast cancer, 34 and EC. 35 In addition, Kho et al performed a bidirectional, two-sample Mendelian randomization analysis to investigate the relationship between levels of three blood lipids and EC risk in a large population.…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol is a vital component in cell membranes and a precursor for steroid synthesis, including androgens. In prostate cancer, high cholesterol and cholesterol biosynthesis have been associated with for example progression [ 48 ], metastasis [ 49 ], and poor treatment response to taxanes [ 50 ]. Together with the downregulation of the cholesterol synthesis pathway by ostecoclasts in the present study, this would indicate a suppressive role of osteoclasts on aggressive features associated with cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the LNCaP cell, an androgen-sensitive line of prostate cancer cells, can directly utilize glutamine for fatty acid production, and so glutamine was identified as a precursor of fatty acids and cholesterol in PC cells [ 48 ], which has been confirmed by subsequent studies [ 50 , 51 ]. This pathway may be due to a process referred to as reductive carboxylation.…”
Section: Glutamine Metabolism Characteristics In Endocrine-related Ca...mentioning
confidence: 90%